Development of Ac- and Ds-tagged starter lines for large-scale transposon-mutagenesis in tomato - Alka Kumari; Rachana Ponukumatla; Arun Kumar Pandey; Yellamaraju Sreelakshmi; Rameshwar Sharma (PLoS ONE, 2025)
Tomato ( Solanum lycopersicum ), a model for fleshy fruit ripening, is predicted to possess ~40,000 genes based on in silico homology-based annotation. However, the functional roles of most annotated genes remain unvalidated. Transposon-tagged mutagenesis offers a powerful strategy for functional genomics, enabling gene identification through phenotypic analysis and activation tagging. Yet, the lack of an efficient in planta transformation system has limited large-scale transposon mutagenesis in tomato. To overcome this limitation, we developed two tomato starter lines, each harboring a maize transposon element: the Dissociation ( Ds ) element and its corresponding Activator ( Ac ) transposase. Crossing these lines induced Ac -mediated transposition of Ds in the F 1 generation. In the F 2 progeny, we tracked the excision and reintegration of Ds across the genome. The Ds insertions were distributed across multiple chromosomes, confirming unlinked transposition. Sequencing of flanking regions revealed random integration into genic, intergenic, and promoter regions. Our study establishes a platform for transposon-tagged mutagenesis in tomato, providing a valuable resource for large-scale functional gene validation.